Innovative development of service organizations in the digital transformation context - V. I. Byvshev; Yu. Yu. Suslova; A. V. Voloshin; I. V. Pisarev (Интеллект. Инновации. Инвестиции)
The study of the issues of innovative development of the service sector is an important area of socio-economic development of modern society, taking into account the processes of digital transformation. All this is due to the fact that today the service sector is becoming one of the key sectors of the economy. In this regard, the purpose of the research is to study the innovative development of service sector organizations in the context of digital transformation. In the course of the study, the authors reviewed existing works in the field of studying the innovative development of the service sector in the context of digital transformation, on the basis of which they concluded about the positive trends in the innovative development of service sector organizations from the introduction of new digital technologies and services. The analysis of statistical information on the innovative development of the service sector was carried out, the innovative activity of service sector organizations was considered, the amount of costs for innovative activities was estimated, including the intensity of spending on innovative activities by service sector enterprises, the nature of the innovative development of the Russian service sector was determined. The paper compares the innovative activity of organizations in Russia with the leading countries in the development of innovations. As a result, the authors conclude that the processes of digital transformation have a significant impact on the development of innovations in service sector organizations, which is confirmed by the analysis of the dynamics analyzed in the study of indicators of innovation activity, the structure of innovations carried out by organizations, the amount of costs for innovative development and an increase in the share of service sector organizations implementing innovations in the digital environment.